Registration of 'WB9879CLP' Hard Red Spring Wheat. Issue 2 (19th March 2013) - Blake, N. K.; Clark, D.; Lanning, S. P.; Carlson, G. R.; Lamb, P. F.; Nash, D.; Wichman, D. M.; Kephart, K. D.; Stougaard, R. N.; Miller, J.; Eckhoff, J. L.; Menalled, F.; et al.
Abstract : 'WB9879CLP' hard red spring wheat ( Triticum aestivum L.) (Reg. No. CV‐1086, PI 666046) was developed by the Montana Agricultural Experiment Station and released in 2012 to the commercial partner Westbred, a subsidiary of Monsanto. WB9879CLP is a two‐gene Clearfield wheat for use with the imidazolinone herbicide Beyond (BASF). WB9879CLP was developed by backcrossing alleles for resistance to the imidazolinone herbicide class into the recurrent parent 'Choteau'. Choteau has solid stems, which provide resistance to the wheat stem sawfly ( Cephus cinctus Nort.). The wheat stem sawfly is a major yield‐reducing pest in large areas of Montana and surrounding regions. Alleles for herbicide resistance at TaAHAS1D and TaAHAS1B were selected during the backcrossing process and line derivation using polymerase chain reaction markers developed by BASF. Two years of replicated yield trials at a total of 16 sites showed that WB9879CLP is similar to Choteau in most agronomic characteristics. WB9879CLP showed no symptoms of damage at any of 13 testing sites when imidazolinone herbicide was applied at two times the recommended rate. WB9879CLP is the first Clearfield solid‐stem wheat variety for sawfly infested sites in Montana and adjoining regions.